Principle of mathematical induction
Here's the statement of the principle of mathematical induction:
For each positive integer \( n \) let \( P(n) \) be a statement. If
- \( P(1) \) is true, and
- \( \forall k \in \natural, P(k) \Rightarrow P(k+1) \)
then, \( \forall n \in \natural, P(n) \) is true.
A proof using this principle is known as an induction proof or a proof by induction.
The first step, the verification of the truth of \( P(1) \) is known as the base step, basis step or the anchor of the induction.
The implication \( P(k) \Rightarrow P(k+1) \) for arbitrary positive integer \( k \) is known as the inductive (or induction) hypothesis.
Establishing the truth of this implication is called the inductive step of the induction proof.
Note that more generally, the principle of mathematical induction is also applied to proofs of the form "For every integer \( n \ge m, P(n) \)" by starting with the base step verifying the truth of \( P(m) \).
Example
Prove: \( \forall n \in \natural, \sum_{i=1}^{n} i = \frac{n(n+1)}{2} \)
Proof:
Let \( f(n) = \sum_{i=1}^n \) and \( g(n) = \frac{n(n+1)}{2} \).
We need to show that \( f(n) = g(n), \forall n \in \natural \).
As the base step, observe that
$$ f(1) = \frac{1(1+1)}{2} = 1 $$
The induction hypothesis is then suppose \( f(k) = \frac{k(k+1)}{2} \). Thus,
\begin{align}
f(k+1) = &~ f(k) + (k+1) \\\\
= &~ \frac{k(k+1)}{2} + (k+1) \\\\
= &~ \frac{k^2 + k + 2k + 2}{2} \\\\
= &~ \frac{(k+1)(k+2)}{2}
\end{align}
Thus, we have shown that if \( f(k) = \frac{k(k+1)}{2} \) for some \( k \in \natural \), then \( f(k+1) = \frac{(k+1)(k+2)}{2} \), thereby completing the induction step.
Hence, \( \forall n \in \natural, f(n) = \frac{n(n+1)}{2} \).